PERCAMPURAN BUDAYA BUGIS DENGAN BUDAYA MELAYU DI DESA PEBENAAN KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Carles, Yulius; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Bugis an ethnic group with origins in South Sulawesi region. The main characteristics of this ethnic group is the language and customs so that the Malay and Minangkabau migrants who migrated to Sulawesi since the 15th century as an administrative personnel and traders in the Kingdom of Gowa and been acculturated, also categorized as the Bugis. Indonesia based on the 2000 census, the population of the Bugis as many as about six million people. Now the Bugis people also spread in various provinces in Indonesia, such as Southeast Sulawesi, Central Sulawesi, Papua, East Kalimantan, and South Kalimantan. Bugis people are also many who migrated to foreign nationals. Bugis are the tribes who belong to the Deutero Malay tribes. Go to the archipelago after the first wave of migration from mainland Asia rather Yunan. The word